Classical and new biomarkers of neonatal sepsis - Machado, Alexandre Paulo (2017)
Objective: to analyze the most used biomarkers in the diagnosis of neonatal sepsis described in literature. Methods: we searched electronic databases of Cochrane Library, PubMed and SciELO, with the following combined descriptors: [Neonatal OR Newborn OR Infants AND Sepsis AND Molecular Markers]. Randomized articles, from 1990 to 2014 dealing with “infectious and/or inflammatory biomarkers involved in neonatal sepsis” which had full version available for free were included. Results: from a total of 655 studies, 283 were included, 47% of inflammation, 37% of inflammation/ infection, and 16% of infection. From those, 184 were available, and most cited markers were: PCR, PCT, IL-6, IL-10, IL-8, TNF-α, CD64, E-selectin, IL-1β, nGAL, TBARS and SAA. Conclusion: diagnosis using biomolecules can be influenced by samples particularities, studied subjects, comorbidities particularities and employed assay. The combined use of molecular markers in neonatal sepsis seems to be a trend, increasingly common in the majority of the researches. Therefore, this review may help in future investigations, since it describes the reported markers for diagnosis of SIRS and neonatal sepsis.